Evaluation of naproxen-induced oxidative stress, hepatotoxicity and in-vivo genotoxicity in male Wistar rats - Mir Hilal Ahmad; Mahino Fatima; Mobarak Hossain; Amal Chandra Mondal (Elsevier, 2018)
Naproxen (NP), a nonsteroidal anti-inflammatory drug (NSAID), is used for the treatment of common pain, inflammation and tissue damage. Genotoxicity testing of NP is of prime importance as it represents the largest group of drugs to which humans are exposed. Not many genotoxic studies are reported on NP; therefore, the present study investigated the detailed genotoxic and oxidative stress properties of NP. Male Wistar rats were administered NP orally at the doses of 38.91 and 65.78 mg/kg body weight for 14 days. Reduced glutathione (GSH), superoxide dismutase (SOD), catalase (CAT) and lipid peroxidation (LPO) activities/levels were measured in the liver, kidney and brain tissues. The aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP) activities, and total bilirubin (TBIL) levels were measured in the liver tissues. Micronucleus frequency (micronucleus test MNT) and DNA damage (comet assay) were performed in the bone marrow cells and leukocytes, respectively. The results showed that NP treatment decreased the GSH levels and increased the SOD, CAT, LPO, ALT, AST, ALP and TBIL activities/levels compared to the control (p < 0.05). Results of MNT showed an increased micronucleus induction and comet assay showed a significant increase in DNA damage in the NP treated animals (p < 0.05). Treatment of NP resulted in the biochemical imbalance and induced oxidative stress that deteriorated the integrity of the cells, which caused significant damage to the genetic material and affected liver function in male Wistar rats. Therefore, NP is a potential genotoxic agent that induces genotoxicity and oxidative stress. Keywords: Genotoxicity, Naproxen, Wistar rat, Antioxidants, Oxidative stress, DNA damage